Need for recovery amongst emergency physicians in the UK and Ireland: a cross-sectional survey. Issue 11 (2nd November 2020) - Cottey, Laura; Roberts, Tom; Graham, Blair; Horner, Daniel; Stevens, Kara Nicola; Enki, Doyo; Lyttle, Mark David; Latour, Jos
Abstract : Objectives: To determine the need for recovery (NFR) among emergency physicians and to identify demographic and occupational characteristics associated with higher NFR scores. Design: Cross-sectional electronic survey. Setting: Emergency departments (EDs) (n=112) in the UK and Ireland. Participants: Emergency physicians, defined as any registered physician working principally within the ED, responding between June and July 2019. Main outcome measure: NFR Scale, an 11-item self-administered questionnaire that assesses how work demands affect intershift recovery. Results: The median NFR Score for all 4247 eligible, consented participants with a valid NFR Score was 70.0 (95% CI: 65.5 to 74.5), with an IQR of 45.5–90.0. A linear regression model indicated statistically significant associations between gender, health conditions, type of ED, clinical grade, access to annual and study leave, and time spent working out-of-hours. Groups including male physicians, consultants, general practitioners (GPs) within the ED, those working in paediatric EDs and those with no long-term health condition or disability had a lower NFR Score. After adjusting for these characteristics, the NFR Score increased by 3.7 (95% CI: 0.3 to 7.1) and 6.43 (95% CI: 2.0 to 10.8) for those with difficulty accessing annual and study leave, respectively. Increased percentage of out-of-hours work increased NFR Score almost linearly: 26%–50% out-of-hours work=5.7 (95% CI: 3.1 to 8.4); 51%–75% out-of-hours work=10.3 (95% CI: 7.6 to 13.0); 76%–100% out-of-hours work=14.5 (95% CI: 11.0 to 17.9). Conclusion: Higher NFR scores were observed among emergency physicians than reported in any other profession or population to date. While out-of-hours working is unavoidable, the linear relationship observed suggests that any reduction may result in NFR improvement. Evidence-based strategies to improve well-being such as proportional out-of-hours working and improved access to annual and study leave should be carefully considered and implemented where feasible.